Implementasi Maqashid Syariah dalam Sidang Itsbat Hilal Penentuan Awal Ramadhan - Ismail, I; Ghofur, Abdul (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
The trial of the initial determination of Ramadhan, Shawwal and Zulhijjah is often a criticism for those who say the initial determination of Ramadhan is in line with the reckoning system, it does not need a congregation hearing that consumes state money, leave it to the community to join the organization it believes. This paper explains the position of the congregation of itsbat to determine the beginning of Ramadan in the perspective of maqashid sharia. By analyzing the practice of the congregation trial and the prevailing rules in Indonesia, it can be concluded that the practice of the trial of the congregation has been classified as perfect for the initial determination of the month of Ramadan. In maqashid syariah, the trial of the initial determination of Ramadhan is included in the category of dharuriyyat in particular and hajiyat in general. The congregation is needed by the Muslim community of Indonesia, considering that to increase the value of benefit and reject the harm which is the core of maqashid sharia is in the trial of itsbat. Therefore, adhering to the congregation of itsbat is to maintain benefit while rejecting harm.